Tinjauan Yuridis Penembakan Tentara Nasional Indonesia Dalam Keadaan Tidak Darurat Menurut Hukum Indonesia - Irwan Triadi; Nurrachma Maharani (Lembaga Pengembangan Kinerja Dosen, 2024)
The military intervention carried out by the Indonesian National Army (TNI) in the conflict in Intan Jaya Regency, Papua, has raised serious concerns regarding compliance with legal standards and human rights (HAM). The actions of the Indonesian National Army (TNI) which resulted in the deaths of three Papuans raise doubts about respect for individual rights to life and security. In conflict situations, it is important to ensure that human rights, especially the right to life, are respected and protected. For example, in Law no. 34 of 2004 which regulates the use of weapons by the Indonesian National Army (TNI) in peaceful conditions, allows the use of weapons only with written permission from superiors and in the context of maintaining security and requested. In the context of this case, the shooting at the Sugapa Community Health Center did not have written permission from the Indonesian National Army (TNI) superiors, which is a serious violation of law. This violation raises questions about the accountability of security forces and the need for law enforcement in cases of gun shooting by members of the Indonesian National Army (TNI) outside of emergency situations. The situation in Papua creates ongoing challenges. Armed groups in the region often threaten national security and the safety of security forces. In the face of serious threats to state sovereignty, the government, and the Indonesian National Army (TNI) may feel forced to take decisive action. However, these actions must still comply with legal and human rights standards and ensure that human rights and the right to life of individuals are fully respected. This research is normative in nature with a focus on analysis of the legal framework that regulates the use of weapons by the Indonesian National Army (TNI). Normative research methods are used to state consistency and compliance with applicable regulations. Through this approach, the research aims to provide a legal perspective on erasure actions in Papua, as well as asking whether these steps are in accordance with applicable legal and human rights principles. It is hoped that the results of this research will provide a basis for recommending improvements to policies and actions that support law enforcement and human rights protection in the context of conflict in Papua